Endophytic Bacteria and Fungi from Indonesian Medicinal Plants with Antibacterial, Pathogenic Antifungal and Extracellular Enzymes Activities: A Review - Jendri Mamangkey; Lucas William Mendes; Arman Harahap; Dana Briggs; Cengiz Kayacilar (Publisher Cv. Inara, 2022)
The habitat of endophytic bacteria in plant tissues making it automatically used by plants to protect themselves against pathogenic bacteria. Endophytic bacteria have been applied in various fields, including agriculture, pharmacy, medicine, and biotechnology. This review was carried out to summarize recent studies focusing on the diversity of endophytic bacteria derived from traditional medicinal plants which have antibacterial activity and extracellular enzymes. This article was prepared and written by referring to literature studies collected from books and online journal publication. The literature review of endophytic bacteria focused on Vernonia anthelmintic, Saurauia scaberrinae, and Ki rinyuh (Chromolaena odorata) plants. The results revealed that endophytic bacteria obtained from Vernonia anthelmintic plant is from Micrococcus, Bacillus, Pseudomonas, Stenotrophomonas, and Pantoea genus which possess the same biological properties as the host plant, producing antibacterial activity. Saurauia scaberrinae plant successfully isolated endophyte fungus Phoma sp. which produces phomodione (4) and cercosporamide. Phomodione (4) exhibit inhibitory activity against S. aureus, P. ultimum, S. sclerotiorum and R. solani. Cercosporamide exhibits inhibitory activity against S. aureus. Endophytic bacteria were also isolated from Ki rinyuh (Chromolaena odorata), including BECB3, BECB 4, BECA 8, BECA 5, BECA 1, and BECA 10 isolates which have extracellular enzyme activities such as ?-amylase, ?-amylase, cellulase, chitinase, and protease. Understanding endophytic bacteria in medicinal plants can help researchers apply them effectively.